The overweight mind and body : your unique psychological journey towards weight loss - Leach, Kathy, 1949- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2022)
"The Overweight Mind and Body is a self-help guide to understanding the psychological issues that lead to overeating and weight gain. The book enables the reader to discover the psychological drives that lead to unwanted weight and to find ways of meeting those drives other than with food. It introduces a simple, user-friendly theory of Transactional Analysis to promote weight-related self-awareness. The author includes exercises that empower readers to uncover their own stories. She understands that, for many, carrying extra weight is emotionally and physically painful and so gently encourages readers to explore at their own level. She uses Case studies to demonstrate the many unconscious influences on one's eating and how, when people discover and resolve these influences, they no longer need extra food. Reading them shows that "you are not alone". This book will also be of interest to, and a useful guide for, practitioners in the caring professions who work with clients struggling with eating and overweight"--
Part I. The Foundations of your journey towards understanding and change; 1. Important things for you to think about as a foundation to your self-exploration; 2. You are worth it; 3. Overeating and Overweight Ẃhat do they mean?; 4. The psychological reasons for unhurried weight loss; 5. How might you sabotage your journey to weight loss?; 6. You are not alone; Part II: Your unique psychological journey towards understanding and weight loss; 7. Looking at your ways of being and doing: The Parent Adult and Child in you; 8. Further focus on how your Child self can influence your eating and weight; 9. Psychological Hungers. Are you hungry for food or is it something else?; 10. What your body size might mean to you; 11. Reconnecting with the body self; 12. The Food distancing Technique; 13. The Power you give to food; 14. The place of body movement in your journey; 15. Recapping, encouragement and concluding thoughts.
Keywords: Obesity -- Psychological aspects; Weight loss -- Psychological aspects; PSYCHOLOGY / Psychopathology / Eating Disorders; PSYCHOLOGY / Mental Health